Financial due diligence for financial intermediaries technical guidance note. (Metro Manila, Philippines Asian Development Bank, 2018)
This technical guidance note describes ADBs requirements and good practices for due diligence on financial intermediation loans.ADB financial intermediation loans are used to further policy reform in the financial and real sectors; strengthen the capacity, governance, and sustainability of participating financial intermediaries; mitigate market distortions; and help increase the efficiency and stability of the respective developing member country financial system. The objective of due diligence is to assess the financial sustainability of financial intermediary and conclude its eligibility for an ADB project, including its financial and risk management capacity.
Keywords: Public sector -- Developing countries; Electronic books